Implementation of the Maternal Reflective Method (MRM) in Islamic Religious Education Learning for Deaf Children - Berutu, Khalisha Awliya; Widodo, Hendro (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2025)
The implementation of the Maternal Reflective Method (MRM) in Islamic Religious Education (PAI) for hearing-impaired children at SLB B Karnnamanohara addresses the need for effective strategies in overcoming barriers to teaching abstract religious concepts. A qualitative approach was applied, involving three PAI teachers and six students with moderate to severe hearing loss from grades VII–IX. Data were obtained through observation, in-depth interviews, and document analysis, and analyzed through data reduction, display, and conclusion drawing. Findings indicate that MRM encourages improved religious understanding and communication skills by combining heart-to-heart conversations, visualization media, and active parental involvement. Although positive outcomes emerged, it remains premature to claim the method’s effectiveness without quantitative validation. These results underscore the importance of integrating MRM with consistent parental collaboration to enhance the religious education experience for hearing-impaired learners